The Potential Fruit Crop of Cibodas Botanical Garden - Suluh Normasiwi; Muhammad Imam Surya (Biosaintifika: Journal of Biology & Biology Education, 2016)
As an institute for ex situ plant conservation of high mountains, Cibodas Botanical Garden (CBG), has more than 1652 species and 8140 specimens of plant collections. An inventory of potential fruit crop in CBG which will support the conservation program had never been done before. The aim of this activity is to determine its potential collections as fruit crop. Descriptive analysis was used to analyze all the data achieved from registration unit and catalogue of (CBG). The results showed that 422 numbers of collections from 31 family, 56 genus and 114 species have high potential as a fruit crop. Moreover, Cibodas Botanical Garden has 74% collection of indigenous fruit (included 85 species) and 61% collection of underutilize fruit (included 68 species) from the total number of fruit plant collections. Most of potential plant collections are able to be developed as an edible fruit crop in Indonesia in order to enhance local food security through diversification of fruit crop.How to CiteNormasiwi, S., Surya, M. I. (2016). The Potential Fruit Crop of Cibodas Botanical Garden. Biosaintifika: Journal of Biology Biology Education, 8(2), 206-213.